A linear additivity water resources assessment indicator by combining water quantity and water quality - Xiaoran Cao (Elsevier, 2021)
Water scarcity is a major problem faced by many parts of the world and seriously affects local development. Most of the previous water resources assessment only considered the water quantity and quality separately, and few studies had converted it into an indicator for assessment. We proposed a linear additivity indicator to calculate the amount of water resources by combining water quantity and water quality. The indicator named Water Quantity and Quality for Water Yield Equivalent (QQWYE). We calculated the water yield in the upstream watershed area of Miyun reservoir near Beijing, China in the year of 2000, 2008 and 2013. At the same time, we also used the QQWYE indicator to calculate the water yield equivalent on the basis of water yield, and made a sensitivity analysis of the results. Then the results of water yield and water yield equivalent were used to assess the amount of water resources. The results showed that the water yield in the study area in 2000, 2008 and 2013 were 372 × 106 m3, 723 × 106 m3 and 700 × 106 m3, respectively, and the water yield equivalent calculated using QQWYE were-206 × 106 m3, 553 × 106 m3 and 509 × 106 m3. This indicates that using the QQWYE indicator to assess water resources is more accurate than calculating water yield alone. In the sensitivity analysis, precipitation and evapotranspiration are highly sensitive to water yield and water yield equivalent, because climate change will significantly affect local precipitation and evapotranspiration. In the future watershed management, water consumption should be saved and water use efficiency should be improved to prevent climate change from having a significant impact on water resources. Beyond that, using a linear additivity indicator QQWYE to assess water resources can meet the principle of conservation of water resources. The calculation results of this study are relatively reliable and can provide a scientific basis for the sustainable management and rational utilization of water resources in the Miyun Reservoir watershed.